URGENSI PERMAINAN TRADISIONAL DALAM MENGEMBANGKAN KECERDASAN SOSIAL ANAK USIA DINI - Nehru Meha (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
Playing is very familiar with the activities of human life. At times people are in the phase of growth and development from childhood to adulthood almost none of individual who do not know "game”. Based on the scientists’ study in the field of psychology, education, social, and humanities, show that game greatly affects the child's development. In the current era of globalization, many traditional games have been abandoned because they affected the various types of modern games. Even if the traditional games are still standing, it is only certain types and in certain places as well. Very relevant when traditional games children were exhumed in connection with the growing dominance of the modern game in the lives of children, as well as an effort to keep the traditional game is not extinct. Traditional games to develop various aspects of intelligence and potential of children and inculcate positive values. Organization of early childhood education requires the right approach to optimize the potential of intelligence of children, including through local cultural approach which is a traditional play.Keywords: Social Intelligence, Early Childhood and Traditional Play